Do porcine Sertoli cells represent an opportunity for Duchenne muscular dystrophy?. (26th March 2019) - Chiappalupi, Sara; Salvadori, Laura; Luca, Giovanni; Riuzzi, Francesca; Calafiore, Riccardo; Donato, Rosario; Sorci, Guglielmo
Abstract: Sertoli cells (SeC) are responsible for the immunoprivileged status of the testis thanks to which allogeneic or xenogeneic engraftments can survive without pharmacological immune suppression if co‐injected with SeC. This peculiar ability of SeC is dependent on secretion of a plethora of factors including maturation factors, hormones, growth factors, cytokines and immunomodulatory factors. The anti‐inflammatory and trophic properties of SeC have been largely exploited in several experimental models of diseases, diabetes being the most studied. Duchenne muscular dystrophy (DMD) is a lethal X‐linked recessive pathology in which lack of functional dystrophin leads to progressive muscle degeneration culminating in loss of locomotion and premature death. Despite a huge effort to find a cure, DMD patients are currently treated with anti‐inflammatory steroids. Recently, encapsulated porcine SeC (MC‐SeC) have been injected ip in the absence of immunosuppression in an animal model of DMD resulting in reduction of muscle inflammation and amelioration of muscle morphology and functionality, thus opening an additional avenue in the treatment of DMD. The novel protocol is endowed with the advantage of being potentially applicable to all the cohort of DMD patients regardless of the mutation. This mini‐review addresses several issues linked to the possible use of MC‐SeC injected ip in dystrophic people.